An Introductory Point-of-Care Ultrasound Curriculum for an Anesthesiology Residency Program - Susan C. Lee; Edward C. Yang; Jovany Cruz Navarro; Charles G. Minard; Xiaofan Huang; Yi Deng (Association of American Medical Colleges, 2022)
Introduction The use of point-of-care ultrasound (POCUS) is a growing trend in the field of anesthesiology. However, formal POCUS curriculums are still not widely implemented in residency programs. As the Accreditation Council for Graduate Medical Education and the American Board of Anesthesiology have both incorporated POCUS into their educational aims and expectations for graduates, we recognized the need for a formal POCUS curriculum for our residency program. We developed and implemented a comprehensive 3-week POCUS curriculum for our first-year anesthesiology residents (CA1s) in the latter half of their academic year. Methods Twenty CA1s participated in this educational activity. The POCUS curriculum spanned seven topics and was given in weekly 2-hour sessions over the course of 3 weeks. Each session was designed with the first hour consisting of a traditional lecture-based presentation followed by live hands-on practice. A pretest on POCUS knowledge was given to every resident before the curriculum, and a posttest and survey were administered afterwards. Results Every CA1 showed an improvement in their posttest scores. The median scores of the pretest and posttest were 49% and 75%, respectively. Survey results were positive, with all of the CA1s agreeing that the POCUS educational materials were appropriate to their level of training and that their POCUS knowledge and technical skills improved after the curriculum. Discussion We have shown that our formal POCUS curriculum improved anesthesiology residents' knowledge as well as resulting in positive views on the implementation of this intervention.